2021
DOI: 10.1002/chem.202004396
|View full text |Cite
|
Sign up to set email alerts
|

A Domino Fusion of an Organic Ligand Depended on Metal‐Induced and Oxygen Insertion, Unraveled by Crystallography, Mass Spectrometry, and DFT Calculations

Abstract: Herein, the reaction of (1‐methyl‐1 H‐benzo[d]imidazol‐2‐yl)methanamine (L1) with Co(H2O)6Cl2, in CH3CN at 120 °C, leading to the 2,3,5,6‐tetrakis(1‐methyl‐1 H‐benzo[d]imidazol‐2‐yl)pyrazine (3), isolated as a dimeric cluster {[CoII2(3)Cl4]⋅2 CH3CN} (2), is reported. When O2 and H2O are present, (1‐methyl‐1 H‐benzo[d]imidazole‐2‐carbonyl)amide (HL1′) is first formed and crystallized as [CoIII(L1)2(L1′)]Cl2⋅2 H2O (4) before fusion of HL1′ with L1, giving 1‐methyl‐N‐(1‐methyl‐1 H‐benzo[d]imidazol‐2‐carbonyl)‐1 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…[ 14 ] A domino amine oxidative self‐coupling and formal [3+3] cycloaddition mechanism is proposed to produce the substituted pyrazine derivative L4 (2,3,5,6‐tetrakis(1‐methyl‐1 H‐ benzo[ d ]imidazol‐2‐yl)pyrazine) from L1 (1‐methyl‐1 H‐ benzo[ d ]imidazol‐ 2‐yl)methanamine (Table S4). [ 15 ] A rare solvothermal domino reaction with up to 14 steps to give a stable triheteroarylmethyl radical L6 ((tris(4‐methyl‐1‐(1‐methyl‐1 H‐ benzo[ d ]imidazol‐2‐yl)‐ 4 H‐ benzo[ d ]imidazo[1,5‐ a ]imidazole‐3‐yl)methyl hydrochloride)) from L1 has also been developed (Table S4). [ 7 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 14 ] A domino amine oxidative self‐coupling and formal [3+3] cycloaddition mechanism is proposed to produce the substituted pyrazine derivative L4 (2,3,5,6‐tetrakis(1‐methyl‐1 H‐ benzo[ d ]imidazol‐2‐yl)pyrazine) from L1 (1‐methyl‐1 H‐ benzo[ d ]imidazol‐ 2‐yl)methanamine (Table S4). [ 15 ] A rare solvothermal domino reaction with up to 14 steps to give a stable triheteroarylmethyl radical L6 ((tris(4‐methyl‐1‐(1‐methyl‐1 H‐ benzo[ d ]imidazol‐2‐yl)‐ 4 H‐ benzo[ d ]imidazo[1,5‐ a ]imidazole‐3‐yl)methyl hydrochloride)) from L1 has also been developed (Table S4). [ 7 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Our group has developed a series of domino reactions between 3d transition metal salts and chelating substrates containing active groups such as amino and hydroxyl groups. [13,14] We have found that the types of the coordinating atoms and the heteroaryl groups have great influences on reaction sequence. Recently, we have developed a domino reaction between CoCl 2 • 6H 2 O and L1 (1-methyl-1Hbenzo[d]imidazol-2-yl)methanamine), which produced the 2,3,5,6-tetrakis(1-methyl-1H-benzo[d]imidazol-2-yl)pyrazine [13] (L4) (Scheme 1, (1) ).…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] We have found that the types of the coordinating atoms and the heteroaryl groups have great influences on reaction sequence. Recently, we have developed a domino reaction between CoCl 2 • 6H 2 O and L1 (1-methyl-1Hbenzo[d]imidazol-2-yl)methanamine), which produced the 2,3,5,6-tetrakis(1-methyl-1H-benzo[d]imidazol-2-yl)pyrazine [13] (L4) (Scheme 1, (1) ). The possible reaction pathway has been proposed and the coordination between Co 2 + and L1 could not only activate the terminal amine group for self-condensation to give imine intermediate (Int 1) but also facilitate the subsequent formal [3 + 3] cycloaddition of Int 1 to give the pyrazine ring.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many reports on Cu-catalyzed C–N coupling of N-sources with cyclic iodoniums are mechanistically ambiguous, with no experimental evidence for the described Cu intermediates therein. Our research group has developed a strategy to track the overall progress of complex reactions through time-dependent electrospray ionization mass spectrometry (TD ESI-MS), which can give detailed information on the chemical species at different reaction times . In this paper, through TD ESI-MS, the generation, development, and termination of all the intermediates including six Cu complexes are characterized, giving sufficient evidence for the mechanism of current transformation.…”
mentioning
confidence: 99%